Study of Bacterial Contamination of Mobile Phones of Anaesthetists and other Doctors in Surgical Departments During Theatre Sessions (Indian Journal of Public Health Research & Development, 2020)
Background: Personal items such as mobile phones are commonly used by doctors working in the operationtheatre. The hands and personal use items of anaesthetic doctors working in the operation theatre may serveas vectors for transmission of nosocomial pathogens among surgical patients. Our aim was to determine themobile phones contamination among anaesthetists working in the operation theatres of anaesthetic doctors.Method : Forty anaesthetic doctors and other surgical department doctors working in the operation theatresat Sri Lakshmi Narayana Institute of Medical sciences, puducherry and Bharath Medical college andHospital, Chennai were enrolled in the study. Swabs from fingertips and keypads of mobile phones weretaken using moist sterile swabs and plated on Mac Conkey and Blood agar plates. The bacteria isolated wereidentified by biochemical tests.Results: Hand washing was performed by 50% (n=20/40) doctors entering the theatre. 95% (n=38/40)brought their mobile phone to the theatre and 80% used it at least once during the theatre session. Bacterialgrowth was detected from mobile phone swabs. Staphylococci were predominantly cultured from allthe specimens tested. Staphylococci 15%, Methicillin- resistant Staphylococcus aureus (MRSA) 10%,pseudomonas 5%, coagulase negative staphylococci 15%,pseudomonas 5% and total 50% anaesthetist andother doctors mobile phones growth were detected.Conclusion: Personal use items of doctors such as mobile phones show a high percentage of bacterialcontamination. Hand washing compliance was moderate among the study population. Thus personal useitems and hands may act as an important source of nosocomial pathogens in the operation theatre settings.Therefore it is important to encourage higher compliance to hand washing practices and routine surfacedisinfection of personal use items brought to the operation theatre.Mobile phone disinfection should be partof infection prevention protocols in Operation Theatre.
Keywords: Mobile Phones, Bacterial Contamination, Nosocomial Infections, Contamination, HealthCare Workers.